A Set-Based Method for Planning Coordinated Trajectories for Skid-Steered Robotic Units Subject to Constraints, Uncertainties, and External Disturbances - Scordamaglia, Valerio; Ferraro, Alessia (IEEE access, 2025)
This paper introduces a method for planning coordinated trajectories for a group of remotely-controlled, skid-steered robotic units with limited motion capabilities, subject to skidding and slipping phenomena. The proposed solution aims to define optimal trajectories that can be simultaneously tracked by the robots while ensuring collision-free motion, even in the presence of unavoidable tracking errors due to the limited authority of the control algorithm. A key feature is that, at the cost of certain degree of conservatism, the robotic units do not require collision avoidance capabilities to solve online coordination problems during motion. From a methodological point of view, the problem of planning robust and coordinated trajectories that ensure collision-free robot movements is formulated as a graph search problem involving semidefinite programming with constraints in the form of linear matrix inequalities. Finally, in order to show the effectiveness of the proposed solution and highlight some of its potential limitations, the results of several numerical and experimental simulations are discussed.